Digital-based instruction: Chances and challenges in English language teaching context - Ningtyas Orilina Argawati; Lilis Suryani (Institute of Advanced Engineering and Science, 2020)
The use of Digital Based Instruction (DBI) nowadays seems to have many obstacles and difficulties. It is due to lack of digital literacy both lecturers and students. Meanwhile, many advantages also emerge through the use of DBI. It becomes the reason for the lecturers to keep on trying to develop their digital literacy to occupy the need of DBI to their English Language Teaching (ELT) class. This study aimed at revealing the chances and challenges of the implementation of DBI. Descriptive qualitative was employed in this study which involved the use of observation and interview as the instruments. The participants of this study were five English lecturers and 200 students. The findings showed that the chances of applying DBI cover activating students, elevating digital literacy, provoking students’ creativity, and creating new application. While some challenges are also emerged. It is due to limited devices and access, and limited digital literacy. The implementation of DBI could provoke the elevation of digital literacy and creativity if we could handle the challenges.